Preparation and characterization of cogon grass natural fiber as a concrete filler for gamma radiation shielding - Mohd Yusof, Yusrina; Othman, Siti Amira (2021)
Concrete is a combination of cement, fine aggregate, coarse aggregate, and water. Concrete has a high shielding potential against gamma radiation from radioactive source. Concretes having a higher attenuation coefficient may be produced by varying the additives of various specific densities to increase the shielding performance. This study uses a cogon grass fiber, an invasive and unwanted grass due to their ability to grow, and disrupt desirable vegetation efficiently as a reinforcement material mixed into the concrete composite to observe its performance in radiation shielding. Natural fiber is known to have a tolerance to post splitting, high energy absorption and increased fatigue resistance of cement-based composites. Cogon grass fibers are use with different percentages of 0%, 0.5%, 1.0% and 1.5% fiber content with four different thicknesses. In this study, the chemical and physical properties of cogon grass were characterized by the hydrolysis process (Chesson Method) and Atomic Force Microscopy (AFM), respectively. The effect of different percentage of cogon grass fiber in concrete with different thickness to linear attenuation coefficient, the difference of linear attenuation coefficient value between lead concrete and cogon grass fiber concrete and half value layer (HVL) were also investigated. The possibility of using cogon grass natural fiber as a block of concrete for gamma radiation shielding was also evaluated based on the results obtained in this study. The results show that the hemicellulose, cellulose and lignin content of raw cogon grass fiber were 27.60%, 36.62% and 6.11%, respectively. AFM micrograph of cogon grass showed a blocky and rough surface. The calculated linear attenuation coefficient of cogon grass fiber showed an increase with the increase of fiber content and thickness. However, lead concrete showed a higher attenuation coefficient and lower HVL value compared to cogon grass fiber. Despite that, cogon grass fiber concrete may have the potential to be used as shielding material with some improvement.